2020
DOI: 10.1101/2020.02.18.954255
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bile Acid pool composition and Gallbladder function are controlled by TGR5 to protect the liver against Bile Acid overload

Abstract: Backgrounds & AimsAs the bile acid (BA) pool composition is of major impact on liver pathophysiology, we studied its regulation by the BA receptor TGR5, promoting hepatoprotection against BA overload.MethodsWT, total and hepato-specific TGR5-KO, and TGR5-overexpressing mice were used in: partial and 90% extended hepatectomies (EH) upon normal, ursodeoxycholic acid (UDCA)- or cholestyramine (CT)-enriched diet, bile duct ligation (BDL), cholic acid (1%)-enriched diet, and TGR5 agonist (RO) treatments. We the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…TGR5, also known as GPBAR1, is widely distributed in the skeletal muscle, white and brown adipocytes, ileum, and enterohepatic tissues except hepatic parenchymal cells. TGR5-dependent pathways are crucial for protecting hepatocytes from injuries, involving improvement of glucose homeostasis, gallbladder dilatation, hepatic inflammation, and energy expenditure (Carino et al, 2017;Ginos et al, 2018;Iracheta-Vellve et al, 2018;Bidault-Jourdainne et al, 2021;Wang et al, 2022). In addition, diminished TGR5 signals were found to be correlated with downregulated secondary bile acids, attributed to alterations in the abundance of bacteria involved in bile acid transformation (Spatz et al, 2021).…”
Section: Bile Acid Receptorsmentioning
confidence: 99%
“…TGR5, also known as GPBAR1, is widely distributed in the skeletal muscle, white and brown adipocytes, ileum, and enterohepatic tissues except hepatic parenchymal cells. TGR5-dependent pathways are crucial for protecting hepatocytes from injuries, involving improvement of glucose homeostasis, gallbladder dilatation, hepatic inflammation, and energy expenditure (Carino et al, 2017;Ginos et al, 2018;Iracheta-Vellve et al, 2018;Bidault-Jourdainne et al, 2021;Wang et al, 2022). In addition, diminished TGR5 signals were found to be correlated with downregulated secondary bile acids, attributed to alterations in the abundance of bacteria involved in bile acid transformation (Spatz et al, 2021).…”
Section: Bile Acid Receptorsmentioning
confidence: 99%
“…Mechanistically, the membrane Takeda G-protein-coupled receptor activation modulates BA composition to become more hydrophilic, and thus protects against cytotoxic BA accumulation. 3 However, if the BA composition became more hydrophobic, it correlates with increased liver injury after PH in human beings and mice. 3 Mouse models with hydrophobic BA composition, including Cyp2c70 knockout and Cyp2a12/Cyp2c70 double-knockout mice, show inflammation and injury in the liver despite having a reduced overall BA concentration.…”
mentioning
confidence: 99%
“…3 However, if the BA composition became more hydrophobic, it correlates with increased liver injury after PH in human beings and mice. 3 Mouse models with hydrophobic BA composition, including Cyp2c70 knockout and Cyp2a12/Cyp2c70 double-knockout mice, show inflammation and injury in the liver despite having a reduced overall BA concentration. 4 In addition, increasing evidence has shown that changes in BA composition can modulate immune responses in the liver and contribute to the pathogenesis of inflammatory diseases.…”
mentioning
confidence: 99%